Association study of new polymorphisms with sudden cardiac death in men - V. N. Maksimov; A. A. Ivanova; P. S. Orlov; D. E. Ivanoshhuk; S. K. Malyutina; V. P. Novosyolov; M. L. Voevoda (Российский кардиологический журнал, 2018)
Aim. To study the association of new polymorphisms with sudden cardiac death (SCD) in men.Material and methods. The SCD group (n=278) was formed using guidelines of the World Health Organization and the European Society of Cardiology. The autopsy material was taken from the men who died suddenly outside the prevention and treatment facilities who underwent medicolegal examination according to a standard protocol. The average age in the SCD group was 53,2±8,7 years. The control group (n=274) was selected by sex and age from the DNA bank formed during the international studies of MONICA and HAPIEE. The mean age of men in the control group was 53.±8,3 years. Genomic DNA was separated from myocardial tissue and venous blood by the method of phenol-chloroform extraction. Rs10503929, rs7121, rs6730157, rs11720524, rs7737692, rs7521023 polymorphisms were tested using real-time PCR. The insertion- deletion polymorphisms rs.0692285 and rs39.7 were genotyped by PCR with flanking primers followed by polyacrylamide gel electrophoresis. Statistical analysis was performed using the SPSS 13.0 software package.Results. By comparison the frequencies of rs7121 genotypes in the studied groups of Novosibirsk, an increase in the proportion of CC genotype carriers in the group with SCD (OR=.6, 95% CI 1,1-2,2; p=0,025) was found. The carriage of the rs.0692285 ID genotype reduces the risk of SCD (OR=0,6, 95% CI 0,4-0,9; p=0,0M). A carriage of the rs39.7 ID genotype increases the risk of SCD (OR=.5, 95% CI 1,1-2,2; p=0,020).Conclusion. The rs7121 of the GNAS gene, the rs.0692285 of the RYR2 gene, and the rs39.7 of the COL1A2 gene are associated with SCD. Rs10503929, rs6730157, rs11720524, rs7737692, rs7521023 polymorphisms do not associate with SCD in the men of Novosibirsk.